2021
DOI: 10.1186/s12890-021-01491-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 23-valent pneumococcal polysaccharide vaccine for the prevention of pneumococcal pneumonia in the elderly with chronic respiratory diseases: a case–control study of a single center

Abstract: Background The effectiveness of the 23-valent pneumococcal polysaccharide vaccine (PPSV23) in preventing pneumococcal pneumonia has been controversial. Methods To evaluate the effectiveness of the PPSV23 in elderly outpatients with chronic respiratory diseases, we carried out a case–control study, including 4128 outpatients aged ≥ 65 years, in the respiratory department. Results There were 320 vaccinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…An additional study from Japan among adults ages 65 and older with chronic respiratory diseases by Mesuda et al found that the odds of all-cause pneumococcal pneumonia were lower in PPSV23-vaccinated patients. The authors also reported a protective effect in a subgroup of patients ages 70 and older [ 4 ]. Although these findings do not align with our study, Mesuda et al did not quantify serotype-specific estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study from Japan among adults ages 65 and older with chronic respiratory diseases by Mesuda et al found that the odds of all-cause pneumococcal pneumonia were lower in PPSV23-vaccinated patients. The authors also reported a protective effect in a subgroup of patients ages 70 and older [ 4 ]. Although these findings do not align with our study, Mesuda et al did not quantify serotype-specific estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the 23-valent pneumococcal polysaccharide vaccine (PPSV23) was approved for use in 1983 for the prevention of pneumococcal disease caused by the 23 Streptococcus pneumoniae serotypes contained in the vaccine. Current data suggests that PPSV23 vaccination is effective in preventing invasive pneumococcal disease (IPD) in adults [ 1 , 2 , 3 , 4 , 5 ], with an estimated effectiveness of 60% to 70% reported by the United States Centers for Disease Control and Prevention (CDC) [ 6 ]. However, there is no consensus regarding PPSV23 vaccination for the prevention of hospitalized CAP due to serotypes contained in the PPSV23.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of PPSV23 have often shown much less protection than did earlier ones (Table 3) [36][37][38][39][40][41]. Possible reasons for reduced vaccine efficacy of PPSV23 in recent years include: (i) persistence of types for which vaccine (PPSV or protein-conjugate vaccine [see below]) [34].…”
Section: Pneumococcal Vaccination In the Antibiotic Eramentioning
confidence: 99%
“…Recent studies of PPSV23 have often shown much less protection than did earlier ones (Table 3 ) [ 36 41 ]. Possible reasons for reduced vaccine efficacy of PPSV23 in recent years include: (i) persistence of types for which vaccine (PPSV or protein-conjugate vaccine [see below]) does not appear to stimulate good protection, e.g., serotypes 3, 19A; (ii) decreasing prominence of PCV13 strains from the population with opening of an ecologic niche for other pneumococcal types; and (iii) the consequent emergence of strains not covered by PPSV23, e.g., types 15A, 23B, 35 and 38 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted among outpatients aged ≥ 65 years with chronic respiratory diseases in Shizuoka General Hospital, Japan, PPSV-23 was proven to be effective in preventing pneumococcal pneumonia among the elderly. Out of 320 patients vaccinated with PPSV-23, 1.88% developed pneumococcal pneumonia compared to 4.05% of the 3898 unvaccinated patients [ 64 ]. The effectiveness of the PPSV-23 vaccine explains why the majority of guidelines recommend the PPV-23 vaccine.…”
Section: Discussionmentioning
confidence: 99%